Cullin3-TNFAIP1 E3 Ligase Controls Inflammatory Response in Hepatocellular Carcinoma Cells via Ubiquitination of RhoB - Liu, Yue; Zhang, Wenjuan; Wang, Shiwen; Cai, Lili; Jiang, Yanyu; Pan, Yongfu; Liang, Yupei; Xian, Jingrong; Jia, Lijun; Li, Lihui; Zhao, Hu; Zhang, Yanmei (Frontiers in Cell and Developmental Biology, 2021)
Rho family GTPase RhoB is the critical signaling component controlling the inflammatory response elicited by pro-inflammatory cytokines. However, the underlying mechanisms of RhoB degradation in inflammatory response remain unclear. In this study, for the first time, we identified that TNFAIP1, an adaptor protein of Cullin3 E3 ubiquitin ligases, coordinated with Cullin3 to mediate RhoB degradation through ubiquitin proteasome system. In addition, we demonstrated that downregulation of TNFAIP1 induced the expression of pro-inflammatory cytokines IL-6 and IL-8 in TNFɑ-stimulated hepatocellular carcinoma cells through the activation of p38/JNK MAPK pathway via blocking RhoB degradation. Our findings revealed a novel mechanism of RhoB degradation and provided a potential strategy for anti-inflammatory intervention of tumors by targeting TNFAIP1-RhoB axis.